2021
DOI: 10.1186/s40168-021-01118-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant developmental stage drives the differentiation in ecological role of the maize microbiome

Abstract: Background Plants live with diverse microbial communities which profoundly affect multiple facets of host performance, but if and how host development impacts the assembly, functions and microbial interactions of crop microbiomes are poorly understood. Here we examined both bacterial and fungal communities across soils, epiphytic and endophytic niches of leaf and root, and plastic leaf of fake plant (representing environment-originating microbes) at three developmental stages of maize at two co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
188
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(231 citation statements)
references
References 100 publications
25
188
3
Order By: Relevance
“…Furthermore, plant rhizobacterial communities respond differently to plant developmental stages than bulk soil bacterial communities based on multiple microbial attributes implemented in this study, such as alpha and beta diversities, community structure, biomarker analysis, and pattern network analysis. Our findings are consistent with previous results showing that plant developmental stages shape the assembly of plant microbiomes (Chaparro et al, 2014;Qiao et al, 2017;Cordovez et al, 2021;Ma et al, 2021;Xiong et al, 2021a). This was similar to the report by Shi et al (2015) who observed that the growth of plants drove the succession of rhizobacteria in the rhizosphere of Avena fatua.…”
Section: Discussion Plant Developmental Stage Strongly Influences The...supporting
confidence: 93%
“…Furthermore, plant rhizobacterial communities respond differently to plant developmental stages than bulk soil bacterial communities based on multiple microbial attributes implemented in this study, such as alpha and beta diversities, community structure, biomarker analysis, and pattern network analysis. Our findings are consistent with previous results showing that plant developmental stages shape the assembly of plant microbiomes (Chaparro et al, 2014;Qiao et al, 2017;Cordovez et al, 2021;Ma et al, 2021;Xiong et al, 2021a). This was similar to the report by Shi et al (2015) who observed that the growth of plants drove the succession of rhizobacteria in the rhizosphere of Avena fatua.…”
Section: Discussion Plant Developmental Stage Strongly Influences The...supporting
confidence: 93%
“… Gao et al (2020) demonstrated that stochastic forces act on fungal community assembly in the leaves and roots of sorghum during the early stages of development. Similarly, Xiong et al (2021) reported that in maize, fungal communities are more strongly driven by stochastic processes during the early stages of plant development, while bacterial communities at the later stages of development. Compared to annual crops like sorghum and maize, the community assembly patterns of perennial halophyte K .…”
Section: Discussionmentioning
confidence: 83%
“…These microorganisms can form complex interactions with plants and have key roles in promoting plant productivity and health (3,4). The plantbacteria interaction has been the basis of bioproducts that promote increased productivity of agricultural crops, especially inoculants with mechanisms that promote plant-growth, nutrient acquisition and increases of plant tolerance and resistance to abiotic stresses and pests attack (5)(6)(7). Most of these interactions occur in the soil-plant interface using specific niches such as the rhizosphere, endosphere and rhizoplane (1,2,8).…”
Section: Introductionmentioning
confidence: 99%